Variation of piezoelectric coefficient and permittivity of piezoactuator with electric field in AVC experiments. (25th September 2016) - Sukesha,; Vig, Renu; Kumar, Navin
ABSTRACT: Piezoelectric coefficient and permittivity of piezoelectric material varies with variation in electric field. In this work, variation of piezoelectric coefficient and permittivity of piezoelectric material with change in applied electric field is considered while actively controlling vibrations of a plate instrumented with piezoelectric patches. Variation of piezoelectric coefficient and permittivity of piezoelectric material with electric field is considered in finite element model of the smart plate. Kalman estimator is used to estimate first three modal displacements and velocities of the smart plate. Experiments are performed using Labview software for two cases: In case 1 effect of electric field on piezoelectric coefficient and permittivity of piezoelectric material is not included in Kalman estimator and in case 2 this effect is considered in Kalman estimator. For the same control gain, more control voltages get applied on the piezoelectric actuator in case 1 as compared to case 2.